Implementasi Akad Wakalah Dalam Pembiayaan Murabahah Pada PT. Bank Nagari Cabang Syariah Batusangka - Ilham Mahdi; Bunga Metrizal; Mince Trila Ningsi; Erliati Siregar; Anggi Kartika NST (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the implementation of the wakalah contract in murabahah financing products at PT. Bank Nagari Syariah Branch Batusangkar and assess its compliance with Islamic principles as stipulated in the fatwa of the National Sharia Council (DSN-MUI). The research adopts a descriptive qualitative approach using observation, interviews, and documentation as data collection methods. The findings reveal that although the bank has applied the wakalah contract administratively, its implementation does not fully comply with the DSN-MUI fatwa, particularly regarding the requirement that the bank must legally own the goods before executing the murabahah contract. Customers are authorized to purchase goods on behalf of the bank, but sufficient documentation proving the bank’s ownership is lacking. This poses a risk of gharar and weakens the validity of the contract. The study recommends establishing Sharia-compliant Standard Operating Procedures (SOPs), enhancing staff literacy in Islamic finance, and strengthening the role of the Sharia Supervisory Board in ensuring contract compliance